2020
DOI: 10.3390/ijerph17103729
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Running Exercise Modalities on Post-Exercise Oxidative Stress Markers in Trained Athletes

Abstract: The aim of this study was to examine the effect of running exercise modality on oxidative stress. Thirteen endurance athletes (age: 21.46 ± 0.66 years) performed three different running exercise modalities (Continuous running exercise (CR): continuous running exercise at 75% of VO2max for 25 min; intermittent running exercise #1 (15/15): intermittent running protocol, 15 s running at 75% of VO2max, 15 s passive recovery, performed for 50 min; intermittent running exercise #2 (30/30): intermittent running proto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 39 publications
2
21
0
Order By: Relevance
“…In this study, plasma MDA levels were analyzed to confirm the changes in OS according to exercise intensity. The results of the present study showed that plasma MDA levels significantly increase in response to exercise regardless to its intensity (MI or HI), which agrees with previous studies [ 24 , 26 ] that reported a significant increase in plasma MDA levels after acute exercise. This phenomenon is believed to result from free radicals produced by exercise that will in turn promote lipid peroxidation.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this study, plasma MDA levels were analyzed to confirm the changes in OS according to exercise intensity. The results of the present study showed that plasma MDA levels significantly increase in response to exercise regardless to its intensity (MI or HI), which agrees with previous studies [ 24 , 26 ] that reported a significant increase in plasma MDA levels after acute exercise. This phenomenon is believed to result from free radicals produced by exercise that will in turn promote lipid peroxidation.…”
Section: Discussionsupporting
confidence: 93%
“…This phenomenon is believed to result from free radicals produced by exercise that will in turn promote lipid peroxidation. Souissi et al [ 26 ] reported that plasma MDA levels increase significantly after intermittent running exercise at 75% of maximal aerobic speed. Moreover, Spirlandeli et al [ 24 ] showed that plasma MDA levels were significantly increased in eight healthy and well-trained males upon acute exercise intervention, as determined by three different methods (high-performance liquid chromatography, thiobarbituric acid reactive species, and 1-methyl-2-phenylindole analyses), which suggested that MDA could be a valuable biomarker of lipid peroxidation following acute exercise.…”
Section: Discussionmentioning
confidence: 99%
“…One-way-ANOVA test results revealed that there was no significant difference in the mean MDA levels in each group (p>0.05). These results are in line with the results of research conducted by Souissi et al 18 concluded that there was an increase in MDA levels in athletes after carrying out physical activity in the form of running. However, these results differ from the results of a study conducted by Azizbeigi et al 19 concluded that there was a significant decrease in malondialdehyde levels after the resistance training intervention for 8 weeks.…”
Section: Discussionsupporting
confidence: 92%
“…In our study we also observed the enhanced amount of AOPP (M30, M120, F30 groups) and AGE (F30 group), i.e., the products of non-enzymatic oxidation and glycation of proteins. Importantly, exercise modality could determine the level of oxidative stress since intermittent running attenuated elevation in AOPP as compared with continuous exercise due to better repair capacities [65]. Products of oxidation and glycation of proteins also enhance the synthesis of pro-inflammatory cytokines/chemokines by inducing NOX activity or stimulating the receptor for advanced glycation end products (RAGE).…”
Section: Discussionmentioning
confidence: 99%